2016
DOI: 10.1021/acs.orglett.6b01301
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotrifluoromethylation of Unactivated Alkenes and Alkynes Enabled by an Electron-Donor–Acceptor Complex of Togni’s Reagent with a Tertiary Amine

Abstract: An electron-donor-acceptor (EDA) complex between Togni's reagent and a tertiary amine has been introduced. The existence of this EDA complex was supported by NMR titration experiments. The hydrotrifluoromethylation of unactivated aliphatic alkenes and alkynes enabled by this EDA complex has also been developed. This hydrotrifluoromethylation protocol is operationally simple and promoted by a tertiary amine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 64 publications
1
57
1
Order By: Relevance
“…The different solvent effects could be exploited to help enhance or suppress a particular reaction pathway. Clean electrophilic R F + reactivity can be expected to be prominent in acceptor solvents, whereas reactions including R F radicals seem to be more pronounced in donor solvents . The different aggregation modes in solution also give insights into the possible preorganization of the reagent and substrate in solution through σ donation, π donation, or hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The different solvent effects could be exploited to help enhance or suppress a particular reaction pathway. Clean electrophilic R F + reactivity can be expected to be prominent in acceptor solvents, whereas reactions including R F radicals seem to be more pronounced in donor solvents . The different aggregation modes in solution also give insights into the possible preorganization of the reagent and substrate in solution through σ donation, π donation, or hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, acid reagent 1 can be activated by nucleophiles such as iodide and tertiary amines . In the latter, the existence of a distinct Lewis acid–base adduct was supported by 1 H NMR titrations, but the formation constant of such an adduct with N ‐methylmorpholine was determined to be quite low (3.83 L/mol) . In contrast, our group found that alcohol reagent 4 forms more stable adducts with Lewis acids through the oxygen atom as a nucleophilic functionality.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…[5] Donor-acceptor complexes are molecular complexes resulting from the association of an electron donor molecule (D) with an electron acceptor molecule (A), which generally demonstrate partial or total electron transfer from Dt oA upon irradiation (Scheme 1b). [7,8] TheN ADH (the reduced form of nicotinamide adenine dinucleotide) is known to form the donor-acceptor complex when bound to the enzyme, [9] however its synthetic analog Hantzsch ester (HE) has not been reported for donor-acceptor complex formation. [7,8] TheN ADH (the reduced form of nicotinamide adenine dinucleotide) is known to form the donor-acceptor complex when bound to the enzyme, [9] however its synthetic analog Hantzsch ester (HE) has not been reported for donor-acceptor complex formation.…”
mentioning
confidence: 99%